Phonological and Lexical Comparison of Pariaman Dialect with Standard Minangkabau - Santi Eka Putri; Fitrawati Fitrawati (Universitas Negeri Padang, 2020)
This research is aim to find the phonological and lexical comparison of Pariaman dialect with standard Minangkabau. This reserach used descriptive method to conduct the research. Data of this research are the transcription of recorded conversation. The participants who act the subject of the study and became the source of data are the people wholive in Padang and the people who live in Pariaman. The research instrument was open word classes that consisted of verb, noun, adjective and adverb which choosen randomly in the data interview. To collect the data, it used the instrument in the form of list as guidance to ask native speakers, this list of words contained 80 basic vocabularies. Moleang (2005) theory to analyze the data which containinformationwere recorded. Recording was done in order to provide a more accurate data, especially regarding the pronounciation of sounds.